Grid Quality Enhancement via Direct Power Control in Photo-voltaic-Integrated Energy Systems - Layate Zakaria (International Journal of Intelligent Systems and Applications in Engineering, 2025)
This paper introduces a Direct Power Control (DPC)-based strategy designed to enhance power quality in grid-connected photovoltaic (PV) systems. The proposed system architecture incorporates a DC/DC boost converter alongside a three-phase inverter, ensuring efficient energy transfer and effective grid interaction. To maximize energy extraction from the PV array, the Perturb and Observe (P&O) algorithm is employed for Maximum Power Point Tracking (MPPT), enabling optimal performance under varying environmental conditions. The DPC methodology directly regulates instantaneous active and reactive power, achieving unity power factor (UPF) operation by maintaining reactive power at zero. The control strategy employs rotating coordinate transformations and precise grid voltage phase tracking, resulting in robust synchronization and improved dynamic behavior. To further simplify the design and improve the grid performances, an LCL filtering stage has been introduced in this work. Hence, the proposed approach demonstrates significant robustness against load disturbances and variability in operating conditions. Through detailed simulations, the system’s performance is validated, showcasing its ability to enhance grid quality, maintain stability, and ensure seamless operation during both transient and steady-state scenarios. The results emphasize the potential of this DPC-based control strategy as an efficient, reliable, and scalable solution for improving grid power quality in PV-integrated energy systems.